The Dynamics of Political Campaign Strategies: A Case Study of PDIP's Victory in the 2024 Langkat Regency Election - Lumongga Sianipar; Windwati Pinem (Ilmu Inovasi Nusantara, 2025)
The dynamics of local political contests in Indonesia often involve complex challenges, ranging from party competition to controversies surrounding candidates. One of the crucial problems faced in the 2024 Langkat Regency Election was the public's skepticism toward the vice regent candidate, which created a risk of declining electability for the Syah Afandin–Tiorita Surbakti pair. In this context, political parties, particularly the Indonesian Democratic Party of Struggle (PDIP), were required to design a strategic and adaptive campaign to secure voter support. The main objective of this study is to analyze the campaign strategy implemented by PDIP in supporting the Syah Afandin–Tiorita Surbakti candidate pair and to examine how these strategies contributed to electoral success despite the controversies encountered. This study employs a qualitative approach with a descriptive method. Data were collected through interviews with party elites and campaign teams, direct observations during campaign activities, and document studies of campaign materials and media coverage. Data were then analyzed thematically to identify patterns in political marketing practices. The findings reveal that PDIP employed a combination of three political marketing approaches: push marketing, which mobilized the party machine across all levels; pull marketing, which highlighted the strengths and vision of the candidates; and pass marketing, which utilized interpersonal networks to strengthen grassroots engagement. These strategies effectively countered negative perceptions, rebuilt the candidate pair's image, and ultimately secured 55% of the vote in the quick count results. The implications of this study emphasize that well-structured political marketing strategies, when integrated with strong party solidarity and emotional proximity to voters, can be decisive in overcoming reputational challenges and ensuring victory in local elections